Rectal Chlamydia trachomatis and Neisseria gonorrhoeae Infections Among Women Reporting Anal Intercourse. Issue 3 (September 2018) - Llata, Eloisa; Braxton, Jim; Asbel, Lenore; Chow, Joan; Jenkins, Lindsay; Murphy, Ryan; Pathela, Preeti; Schumacher, Christina; Torrone, Elizabeth
Abstract : OBJECTIVE: To examine the prevalence and treatment of rectal Chlamydia trachomatis and Neisseria gonorrhoeae infections among women reporting receptive anal intercourse in a network of sexually transmitted disease or sexual health clinics and estimate the proportion of missed infections if women were tested at the genital site only. METHODS: We conducted a cross-sectional analysis of C trachomatis and N gonorrhoeae test results from female patients reporting receptive anal intercourse in the preceding 3 months during visits to 24 sexually transmitted disease clinics from 2015 to 2016. Primary outcomes of interest were 1) anatomic site-specific C trachomatis and N gonorrhoeae testing and positivity among women attending selected U.S. sexually transmitted disease clinics who reported receptive anal intercourse and 2) the proportion of rectal infections that would have remained undetected if only genital sites were tested. RESULTS: Overall, 7.4% (3, 743/50, 785) of women reported receptive anal intercourse during the 2 years. Of the 2, 818 women tested at both the genital and rectal sites for C trachomatis, 292 women were positive (61 genital only, 60 rectal only, and 171 at both sites). Of the 2, 829 women tested at both the genital and rectal sites for N gonorrhoeae, 128 women were positive (31 genital only, 23 rectal only, and 74 at both sites). Among women tested at both anatomic sites, the proportion of missed C trachomatis infections would have been 20.5% and for N gonorrhoeae infections, 18.0%. CONCLUSION: Genital testing alone misses approximately one fifth of C trachomatis and N gonorrhoeae infections in women reporting receptive anal intercourse in our study population. Missed rectal infections may result in ongoing transmission to other sexual partners and reinfection. Abstract : Genital testing alone misses approximately one fifth of Chlamydia trachomatis and Neisseria gonorrhoeae rectal infections in women reporting receptive anal intercourse in our study population.